Immunologic response to first booster vaccination in dogs treated with zenrelia™ (ilunocitinib tablets) at up to three times the recommended therapeutic dose compared to untreated controls - Genevieve M. Fent; Jay Jacela; Rodrigo Plazola-Ortiz; Jeremiah Olps; Erin E. McCandless; Céline E. Toutain; Sandra O’Kelley; Stephen King (BMC Veterinary Research)
Abstract Background This prospective, non-inferiority study was designed to evaluate the serologic response to booster vaccination in dogs previously vaccinated according to standard of care practice and treated for 56 days with up to 3X the recommended label dose of ilunocitinib. Vaccination occurred 28 days post-treatment initiation and continued through day 56. Measured study parameters included: vaccine-induced serum antibody titers at 15- and 28-day post-vaccination, along with hematological and clinical chemistry parameters. Results Serum antibody titer levels were not significantly different between the control and ilunocitinib treated groups (1X and 3X), and both met the non-inferiority criteria versus the control group after 56 days of treatment (SD 56). All dogs administered ilunocitinib had titers at or above threshold for rabies, CAV-2, and CPV at 15- and 28-day post-vaccination timepoints (SD 43 and SD 56, respectively). The percentage of dogs with titers at or above threshold on SD 43 for CDV were 96, 100, and 95% in the control, 1X and 3X groups, respectively. By SD 56, the percentage of animals with titers above threshold for CDV were similar to pre-vaccination levels in all groups. Conclusion This study demonstrated treatment with ilunocitinib at 1X or 3X the therapeutic dose for 56 days did not significantly attenuate the serologic response to CAV-2, CPV, CDV or rabies booster vaccinations compared to untreated control animals. All animals remained clinically healthy during the study, with only mild gastrointestinal or skin abnormalities typical of laboratory dogs or JAK inhibitor therapy.